Case reportPitfalls in the management of hypocalcaemia: refractory hypocalcaemia after thyroidectomy not caused by postoperative hypoparathyroidism - Skowrońska-Jóźwiak, Elżbieta; Lewandowski, Krzysztof; Lewiński, Andrzej (Archives of Medical Science, 2007)
A 29-year-old patient was admitted with tetany and severe hypocalcaemia despite treatment with high dose alphacalcidol and calcium. Six years earlier she was treated with subtotal thyroidectomy for non-toxic goitre in the Department of Surgery. Postoperatively she required replacement with 100 µg/day of L-thyroxin, but was lost to formal endocrine follow-up. Five years later she presented with non-specific abdominal discomfort and occasional diarrhoea. Examination revealed positive Chvostek’s and Trousseau’s signs, while plasma calcium, decreased to 1.8 mmol/l (ref. range: 2.2-2.55), was thought to be related to hypoparathyroidism caused by thyroidectomy. In view of slightly raised TSH the dose of L-thyroxin was gradually increased to 150 µg. Hypocalcaemia, however, failed to normalise, and in fact worsened, despite gradual increase in the dose of alphacalcidol, and denial of compliance problems with her medication. She was then admitted to hospital. The combination of low calcium, normal phosphate, iron-deficiency anaemia together with poor response to oral medication raised a possibility of malabsorption rather than a simple post-thyroidectomy hypoparathyroidism. Repeated gastroscopy was performed and demonstrated villous atrophy consistent with coeliac disease. Measurement of PTH concentrations of 63.6 pg/ml (ref. range: 15-65 pg/ml) confirmed the presence of functional parathyroids. She was started on a gluten-free diet. Her calcium levels are now normal and the dose of alphacalcidol is being decreased. In conclusions, hypocalcaemia after thyroidectomy cannot be automatically assumed to be caused by post-operative hypoparathyroidism and/or compliance problems. Other possible causes of hypocalcaemia should be considered and appropriately investigated.